A holiday yarn - Goldenbaum, Sally (Goldenbaum, Sally. Seaside knitters mystery., 2010)
With the Seaside Knitters' help, Mary Pisano converts her charming inherited home into a B&B. Her first week is booked by her very own family, in town to discuss their grandfather's will. She's hoping the tranquility of the setting will smooth over ill feelings among family members. But when her cousin Pam-a Sea Harbor, Massachusetts, native-is found murdered, she realizes she was dead wrong... With the holiday cheer severely disrupted, Mary relies on the Seaside Knitters to set things right. They gladly offer their skill for unraveling crime, but it'll take all their crafty know-how to unravel this deadly tangle.